System Dynamics Modelling for Tourism Carrying Capacity in Saba Budaya Baduy - Yakti, Suluh Widya; Sriwana, Iphov Kumala; Rumanti, Augustina Asih (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
Saba Budaya Baduy serves as a significant tourist destination contributing to the local economy of the Baduy community. However, the substantial surge in tourist arrivals poses potential long-term challenges for the local Baduy community. The issues arising from tourism activities encompass cultural shifts, environmental changes, and impacts on the local economy. This research aims to propose a sustainable visitor limitation model to ensure that elements linked to the interests of tourism business activities remain unaffected by visitor restrictions. Quantitative methods apply the Tourism Carrying Capacity (TCC) approach to determine visitor benchmarks and System Dynamics (SD) for simulating visitor limitations over ten year. Model 3, proposed as a policy, yields sustainable visitor limitation policies. The proposed measures include phased visitor limitations annually, price adjustments, agreements between managers and tour operators, and feedback agreements between managers and local businesses. Simulation results from Model 3 project that the TCC-defined visitor limitation value will be achieved by the 10th year (2030), totaling 16,406 visitors annually, compared to an Effective Carrying Capacity (ECC) of 15,612 visitors annually. These measures enhance the local socio-economic resilience through the assurance of annual income stability.